Analyzing Rejection of Corpse Infected by Covid 19 in the Perspective of Moral Panic and Fiqh Sosial Theories - Muhammad Labib (Santri: Journal of Pesantren and Fiqh Sosial, 2020)
This research discusses an interdisciplinary study of Covid 19 excesses that is currently affecting the world, including Indonesia. There were cases of stigma and rejection of corpse infected by Covid 19 that occurred in Banyumas, Lampung, Gowa, South Sulawesi, and Semarang. The theory used as an analytical tool is Stanley Cohen's theory of moral panic to understand the background of community actions, and subsequently uses the social fiqh theory to reinforce the building of an argument for scientific response to the case. The method used in this research is library research by making effective data obtained from reliable online news, journals, and books that can be accounted for. The results of this study are: (1) The perspective of Stanley Cohen's moral panic theory explained that the case of the rejection of the corpse of Covid 19 was triggered by excessive public panic and anxiety until "social / health panic" is closely related to the term "moral panic" in Cohen's theory. This gives the consequence of giving stigma and discrimination of Covid 19. (2) The perspective of social Fiqh with the application model of Madzhab Qauli, the act of refusing a corpse infected with Covid 19 is “a wrong way" in Islamic legal norms. This claim of Islamic law is considered to be in harmony with the maqashid syairah which is understood from Abdul Majid Najjar's thoughts about the maqasid hifdzu al karamah al insaniyyah.